Q. 4 D4.5( 11 Votes )

If <span lang="EN

Formula used.

(a + b)3 = a3 + b3 + 3ab(a + b)

If

x + = 2√7

(a + b)3 = a3 + b3 + 3ab(a + b)

Put a = x and b =

(x + )3 = x3 + 3 + 3 × x × × (x + )

(2√7)3 = x3 + + 3 × (2√7)

56√7 = x3 + + 6√7

x3 + = 56√7 – 6√7

x3 + = √7 [56 – 6]

= 50√7

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

In each of the foWest Bengal Board - Mathematics

If <span lang="ENWest Bengal Board - Mathematics

If we subtract <sWest Bengal Board - Mathematics

Let us write a raWest Bengal Board - Mathematics

Let us rationalizWest Bengal Board - Mathematics

Let us write the West Bengal Board - Mathematics

Let us write whetWest Bengal Board - Mathematics

Let us fill up thWest Bengal Board - Mathematics

Let us divide firWest Bengal Board - Mathematics

The product of <sWest Bengal Board - Mathematics